2001
DOI: 10.1074/jbc.m009454200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CCAAT Displacement Protein (CDP/cut) as a Locus-specific Repressor of Major Histocompatibility Complex Gene Expression in Human Tumor Cells

Abstract: The human MHC 1 class I genes encode the highly polymorphic HLA class I antigen heavy chains, membrane-spanning proteins that combine with the invariant ␤ 2 -microglobulin to form the HLA class I surface antigen (1). Classical MHC class I (HLA-A, -B, and -C) antigen expression is essential for processing and presentation of peptide antigens to cytotoxic CD8ϩ lymphocytes (2). In addition, recent evidence suggests that certain classical and nonclassical class I antigens play an important role in inhibition of na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…Locus-specific down-regulation of major histocompatibility class I gene expression is frequently observed in human tumors, leading to decreased susceptibility to cytotoxic T-cell-mediated lysis. The identification of human CDP as a locus-specific repressor of HLA-B and C gene expression (Snyder et al, 2001) provided further clues that suggest that CDP may be an important player in human hepatocarcinogenesis. Further research on CDP might lead to targets for pharmacologic or gene therapeutic strategies against human hepatocellular carcinoma.…”
Section: Repression Of C/ebp-␣-mediated Transactivation By Caat Displmentioning
confidence: 99%
“…Locus-specific down-regulation of major histocompatibility class I gene expression is frequently observed in human tumors, leading to decreased susceptibility to cytotoxic T-cell-mediated lysis. The identification of human CDP as a locus-specific repressor of HLA-B and C gene expression (Snyder et al, 2001) provided further clues that suggest that CDP may be an important player in human hepatocarcinogenesis. Further research on CDP might lead to targets for pharmacologic or gene therapeutic strategies against human hepatocellular carcinoma.…”
Section: Repression Of C/ebp-␣-mediated Transactivation By Caat Displmentioning
confidence: 99%
“…The DNA binding proteins are transcriptional repressor proteins, some of which have been identiWed such as CCAAT displacement protein (CDP), special AT-rich sequence binding protein 1 (STAB-1), and pancreatic-duodenal homobox factor-1 (PDX-1) [52,53]. It has been shown that SATB1 and CDP negatively regulate several viral and cellular genes through interaction with histone deacetylase and histone lysine methyltransferase [54][55][56][57]. CDP is a known transcriptional repressor protein that has eVects on other viruses such as human papilloma virus and murine leukemia virus [58][59][60][61].…”
Section: The Divergent Promoters Xanking the CMV Enhancersmentioning
confidence: 99%
“…The three loci can be expressed at different levels in different cell types (3,4). The expression of a particular locus can be extinguished in tumor cells, which might contribute to immune evasion (3,5). In contrast, some tumor cell lines express relatively high levels of HLA-C mRNAs (4), which might be protective against NK cells (6).…”
mentioning
confidence: 99%